Treatment of waldenstrom's macroglobulinemia with thalidomide - Dimopoulos, M.A.; Viniou, N.; Zomas, A.; Grigoraki, V.; Galani, E.; Matsouka, C.; Economou, O.; Anagnostopoulos, N.; Panayiotides, P. (Blood, 2000)
Thalidomide is an active agent in patients with refractory multiple myeloma. Based on these data we performed a phase II study in order to evaluate the activity of thalidomide in Waldenstrom's macroglobulinemia (WM). Thalidomide was administered on a doseescalating schedule of 200 mg daily p.o. x 14 days with dose escalation by 200 mg every two weeks to a maximum dose of 600 mg. Twenty patients were treated with a median age of 74 years (range: 48 to 85 years). Hemoglobin was < 10.0 gr/dl in 5 patients, serum monoclonal IgM was >3.0 gr in 9 patients and lymphadenopathy and splenomegaly were present in 7 and 10 patients respectively. Ten patients were previously untreated, 1 was relapsing off treatment, 5 were primary refractory and 4 were treated during refractory relapse. Five patients (25%) achieved at least 50% reduction of serum monoclonal IgM and at least 50% reduction of tumor at all involved sites. At least 25% reduction of IgM was noted in all eventual responders within 4 weeks of thalidomide treatment. Responses occurred in 3 of 10 previoulsy untreated patients and in 2 of 10 pretreated patients. One responding patient with artial fibrillation died of an embolie cerebral accident 4 months after achieving a response and the other responding patients remain without progression for 2+ months to 12 + months. Some degree of toxicity was observed in almost all patients. Grade 2 or 3 toxicities included constipation in 6 patients, somnolence in 3 patients, tremor in 2 patients and neuropathy in 2 patients. This explained the inability to reach the targeted dose of thalidomide 600 mg p.o. QD in all but 4 patients; the median daily dose of this agent was 200 mg. We conclude that thalidomide has moderate activity in WM. A relatively low median daily dose could be administered to this elderly patient population.